Microsurgical Removal of a Deep-Seated Thalamic Lesion in a Child: Case Report (Herald of the National Children's Medical Center, 2025)
This abstract presents a clinical case of the removal of a deeply located thalamic tumor in a child. Despite advances in modern neurosurgical approaches, thalamic tumors remain among the most challenging targets for surgical intervention due to their proximity to vital structures. The authors demonstrated the possibility of optimizing microsurgical access to preserve the anatomical and functional structures of the brain and improve the patient's quality of life.
Keywords: deep-seated brain tumors; pediatric neurosurgery; thalamus; microsurgery